Fundamentals of Public Security Intelligence Activities in Brazil (Interdisciplinary Studies Journal, 2021)
Intelligence Activity is supported by its own doctrine, which guides and disciplines the handling of sensitive material, the object of its use in the development of the knowledge construction process. It has a specific, unique language, whose mastery is essential for professionals in the field, as well as for the users of their work, providing unity of thought, procedure, and language. The intelligence doctrine consists of a set of principles, concepts, norms, values, and ethical assumptions that govern the Activity, mainly regarding the behavior of its professionals. It is characterized by its normative content, the dynamism of its principles, the absence of dogmas, the consensual acceptance of its precepts, and the unity of thought, procedure, and language among professionals in the field. Mastery of this language is essential for intelligence work to proceed without distortions or misunderstandings, as some expressions correspond to what they actually represent, while others have a special meaning that requires deeper understanding. The differences between data, information, and knowledge for intelligence were highlighted, as these distinctions are also relevant in other areas of knowledge. The work utilized an exploratory methodology and theoretical review to obtain its results. At the end of the research, it was concluded that the information activity is guided by principles and characteristics that direct it. The principles identified were interaction, scope, objectivity, secrecy, opportunity, permanence, precision, compartmentalization, simplicity, control, and impartiality. The characteristics obtained were knowledge production, advisory, truth with meaning, data gathering, security, dynamics, coverage, initiative, economy of resources, and specialized actions. It was possible to better understand the pillars of an activity that, although secretive, is present in the daily life of Brazilians, even though they are often unaware of what is happening.
Keywords: Intelligence; Public Security; Fundamentals; Brazil